In service of the nation : CISR's contributions to national Development - Council of Scientific & industrial Research (New Delhi, 1988)
This year India is celebrating the 40th Anniversary of its Independence. This gives us an opportunity to look back and review the contributions made by the Council of Scientific and Industrial Research towards national development. At its inception the Council was assigned a number of important tasks
Keywords: Council of scientific & Industrial Research